O alagamento sazonal afeta a estrutura taxonômica e funcional das assembleias de aves do sub-bosque de ilhas fluviais na Amazônia Central - (:unkn) unknown (Universidade Federal do Amazonas, 2021)
Environmental disturbances are temporary changes that affect species’ populations and assemblages. The effects of environmental disturbances can be measured with indexes that explore the taxonomic and functional components of biological assemblages. Seasonal inundation of the Amazon floodplains represents a large-scale natural disturbance. In this study, we investigated how understory bird assemblages are affected by seasonal flooding. We used indicators of taxonomic and functional structure to compare bird assemblages of river islands with those found in terra firme forest, not affected by seasonal flooding. Understory birds were sampled with mist nets during the non-flooded season in the region of Jaú and Anavilhanas national parks. The understory of river islands presented lower species richness and diversity and higher dominance compared to terra firme forests. River islands and terra firme forests contained very distinct bird assemblages with only 13 species (11% of all sampled species) shared between habitats. Birds that eat invertebrates were more abundant in terra firme forests, while piscivorous species were captured exclusively on river islands. The island bird assemblage also presented a higher abundance of birds that forage alone or in pairs. In contrast, birds that join mixed-species flocks were more abundant in terra firme forests. Functional richness was higher on river islands, while functional evenness was higher in terra firme forests. In addition, the terra firme assemblages presented higher functional divergence. Functional dispersion was similar between habitats. The taxonomic and functional responses of bird assemblages to seasonal flooding are complex and vary depending on the specific diversity metrics and functional components used. Seasonal disturbance in the river island understory may affect bird assemblages through habitat structure or food availability.
Keywords: Várzeas - Amazonas; Ecologia de várzeas - Amazônia; Aves - Amazônia; Florestas de várzea - Amazonas; CIENCIAS BIOLOGICAS; CIENCIAS BIOLOGICAS: ZOOLOGIA; CIENCIAS BIOLOGICAS: ECOLOGIA; Arquipélagos fluviais; Distúrbio ambiental; Diversidade funcional; Pulso de alagamento; Florestas alagáveis